The effect of special exercises by using training methods to develop the kinetic response speed& kinetic speed of scoring goals skill for young footballers - Lazam, Asaad; Jasim, Ali (Journal of Physical Education, 2016)
Emerged the research problem through the experience of the researcher thebudget as a player before and coach and teacher currently observed in the building processes,particularly in the Youth League having a slow response speed motor and the speedperformance of the motor in the course of matches as well as a vaccine researcher with mostof the trained youth found that most of them don't care in the preparation of exercisesespecially the speed of motor response speed performance and motor skill scoring Goalsearch the preparation of exercises using special means of training and to identify the effectof exercises using special training aids in the development of speed of response andperformance motor skill scoring for young players in football, the researcher used theexperimental method two groups state corresponding to two control and experimental ,theresearcher tested the research sample of players youth ,has divided the remaining sample is(20) players into two groups, experimental and Officer of each group (10) players and, ofcourse, desultory ,.The authors concluded that the use of Exercise, using appliances and toolsrunning on the development level and speed of motor response and speed performance of themotor skill of scoring has the players of youth football. And the researcher recommended thenecessity of the use of exercises using special means to desist, devices, tools and means tohelp impact positive in the development of the development speed of motor response andspeed management skills in soccer.